2000
DOI: 10.1002/(sici)1097-4695(200004)43:1<1::aid-neu1>3.3.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Stage-specific effects of bone morphogenetic proteins on the oligodendrocyte lineage

Abstract: Oligodendrocyte maturation is regulated by multiple secreted factors present in the brain during critical stages of development. Whereas most of these factors promote oligodendrocyte proliferation and survival, members of the bone morphogenetic protein family (BMPs) recently have been shown to inhibit oligodendrocyte differentiation in vitro. Oligodendrocyte precursors treated with BMPs differentiate to the astrocyte lineage. Given that cells at various stages of the oligodendrocyte lineage have distinct respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 0 publications
3
19
1
Order By: Relevance
“…Furthermore, even when the OPCs were cultured in proliferation media which should maintain an OPC state, BMP4 treatment decreased Pdgfra mRNA expression in a dose‐dependent manner. This finding was inconsistent with other studies that demonstrated no effect 16, 57 or even a positive effect 43 of BMP4 on OPC proliferation. However, recent studies have suggested that the effects of BMP4 on stem cell proliferation are dose‐dependent; low dose BMP4 increases proliferation, but high dose BMP4 decreases proliferation of mesenchymal stem cells 53 or primordial germ cells 31.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, even when the OPCs were cultured in proliferation media which should maintain an OPC state, BMP4 treatment decreased Pdgfra mRNA expression in a dose‐dependent manner. This finding was inconsistent with other studies that demonstrated no effect 16, 57 or even a positive effect 43 of BMP4 on OPC proliferation. However, recent studies have suggested that the effects of BMP4 on stem cell proliferation are dose‐dependent; low dose BMP4 increases proliferation, but high dose BMP4 decreases proliferation of mesenchymal stem cells 53 or primordial germ cells 31.…”
Section: Discussioncontrasting
confidence: 99%
“…It has been known that BMPs are concerned with regulating the production of both oligodendrocytes and astrocytes. Application of BMPs to cultured cells inhibited the production of oligodendrocytes and facilitated the generation of new astrocytes in vitro (Grinspan et al, 2000;See et al, 2004). During development, overexpression of BMP4 showed both the decrease in oligodendrogenesis and the facilitation of astrogenesis in vivo (Gomes et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression studies of BMPs include the addition of BMPs to in vitro culture systems which inhibits differentiation of OPCs and myelin protein expression but promotes astrocyte development (Grinspan et al, 2000;Gross et al, 1996;Mabie et al, 1997;See et al, 2004). In vivo experiments in which BMPs are overexpressed from neuron-specific promoters, or are over-expressed locally via bead implantation in Xenopus or implantation of BMPoverexpressing cells in chick indicate that BMPs promote astrogliogenesis while inhibiting oligodendrocyte development (Gomes et al, 2003;Mekki-Dauriac et al, 2002;Miller et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…To further confirm that BMP signaling was completely disrupted in the oligodendrocyte lineage in double mutant animals, we investigated whether BMP4 was able to inhibit oligodendrocyte differentiation or induce type II astrogliogenesis of OPCs from double mutant animals, both well-known effects of BMPs on cultured OPCs (Grinspan et al, 2000;Mabie et al, 1997). Cultures from normal and Bmpr double knockout animals were placed in differentiation medium and treated with 50ng/ml BMP or left untreated for two days.…”
Section: Bmp Signaling In the Oligodendrocyte Lineage Is Disrupted Inmentioning
confidence: 99%
See 1 more Smart Citation